Theoretical Analysis of Surface Settlement During Parallel Construction of a Double-Track Tunnel with Small Spacing - Yanao Liu; Yanfeng Li; Guojie Chen; Yuanhui Li; Jialong Li; Jiaxu Jin (Buildings)
The construction of urban subway tunnels typically induces soil settlement within a specific radius of the surrounding area. However, the accuracy of current methods for predicting ground deformation curves corresponding to the excavation of double-track tunnels with small spacing remains insufficient. Most studies simplify this problem by modeling it as a two-dimensional plane problem; however, the actual ground deformation exhibits pronounced three-dimensional characteristics. Consequently, studying the ground settlement patterns caused by the construction of small-spacing double-track tunnels is crucial. This study is based on the Peck formula, used to calculate surface settlement caused by the excavation of single-track tunnels. By incorporating the maximum settlement offset e and the soil loss rate η(y), the soil displacement calculation formula is derived for small-spacing double-track tunnel excavation. The accuracy of the derived formula is then validated through a case study. The findings provide a theoretical reference for predicting surface settlement induced by the excavation of small-spacing double-track tunnels. Furthermore, the influence of different parameters on ground settlement patterns is explored. The results indicate that appropriately increasing the tunnel spacing, increasing burial depth, and adopting a sequential excavation method for the two tunnels help reduce ground settlement.